Interactive sound propagation for dynamic scenes using 2D wave simulation - Rosen, Matthew; Godin, Keith; Raghuvanshi, Nikunj (Computer Graphics Forum (Symposium on Computer Animation), 2020)
We present a technique to model wave-based sound propagation to complement visual animation in fully dynamic scenes. We employ 2D wave simulation that captures geometry-based diffraction effects such as obstruction, reverberation, and directivity of perceptually-salient initial sound at the source and listener. We show real-time performance on a single CPU core on modestly-sized scenes that are nevertheless topologically complex. Our key ideas are to exploit reciprocity and use a perceptual encoding and rendering framework. These allow the use of low-frequency finite-difference simulations on static scene snapshots. Our results show plausible audio variation that remains robust to motion and geometry changes. We suggest that wave solvers can be a practical approach to real-time dynamic acoustics. We share the complete C++ code of our "Planeverb" system [source repo].